POTRET PENDIDIKAN AKUNTANSI SYARIAH DI INDONESIA - RINI RINI (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
This research aims to look at sharia accounting education in Indonesia. Sharia accounting education discussed consists of: history of teaching sharia accounting courses, types of courses taught and challenges in teaching sharia accounting courses. This research uses convenience sampling, namely from universities in the Direktorat Pendidikan Tinggi Islam and in the Direktorat Pendidikan Tinggi. Data comes from the University's website and minutes of meetings of sharia accounting experts, carried out by the Indonesian Institute of Accountants. Sharia accounting courses in Indonesia from 2000-2007 were offered at Trisakti University, Brawijaya University, University of Indonesia and UIN Jakarta. Teaching Islamic accounting is dominated by Islamic banking accounting. The main challenge in teaching Islamic accounting is the lack of textbooks.